Calculation of photon counting distribution in fluorescence intensity fluctuations registration systems - Skakun, Viktor V.; Apanasovich, Vladimir V. (Journal of the Belarusian State University. Physics, 2023)
The study of the molecular composition of a substance based on the calculation of photon counting distribution is an effective method for analysing experimental data in fluorescence fluctuation spectroscopy. This method is non-invasive and makes it possible to resolve the processes of dimerisation of molecular complexes in living cells, which is in demand in biology, medicine and pharmaceuticals. Obtaining a theoretical photon counting distribution is a complicated task in both algorithmic and computational sense. In this paper, a comparative analysis of the three main methods for calculating photon counting distribution is carried out and an effective method for its calculating is proposed, which guarantees the correct calculation of photon counting distribution over the entire range of variation of the model parameters and the width of the counting time interval. The derivation of all expressions is given for the case of a Gaussian approximation of the brightness profile with correction for out-of-focus emission and normalisation to the first two moments of the profile. Other ways of approximating the brightness profile and normalising the estimated parameters can be made similarly. The proposed technique is implemented in FFS Data Processor software package, which is designed for a global analysis of photocounts in fluorescence fluctuation spectroscopy and allows efficient calculation of photon counting distribution in a wide range of estimated parameters.